Comparative analysis of genome-encoded viral sequences reveals the evolutionary history of flavivirids (family Flaviviridae). Issue 2 (6th September 2022) - Bamford, Connor G G; de Souza, William M; Parry, Rhys; Gifford, Robert J
Abstract: Flavivirids (family Flaviviridae ) are a group of positive-strand ribonucleic acid (RNA) viruses that pose serious risks to human and animal health on a global scale. Here, we use flavivirid-derived deoxyribonucleic acid (DNA) sequences, identified in animal genomes, to reconstruct the long-term evolutionary history of family Flaviviridae . We demonstrate that flavivirids are >100 million years old and show that this timing can be combined with dates inferred from co-phyletic analysis to produce a cohesive overview of their evolution, distribution, and diversity wherein the main flavivirid subgroups originate in early animals and broadly co-diverge with major animal phyla. In addition, we reveal evidence that the 'classical flaviviruses' of vertebrates, most of which are transmitted via blood-feeding arthropod vectors, originally evolved in haematophagous arachnids and later acquired the capacity to be transmitted by insects. Our findings imply that the biological properties of flavivirids have been acquired gradually over the course of animal evolution. Thus, broad-scale comparative analysis will likely reveal fundamental insights into their biology. We therefore published our results via an open, extensible, database (Flavivirid-GLUE), which we constructed to facilitate the wider utilisation of genomic data and evolution-related domain knowledge in flavivirid research.